TRANSLATING PRONOUNS, PROPER NAMES AND KINSHIP TERMS FROM INDONESIAN INTO ENGLISH AND VICE VERSA - Izak Morin (TEFLIN, 2005)
This paper presents differences in pronominal system, proper name, and kinship terminology of both Indonesian and English which affect translation work. Such differences are discussed in detail by providing examples that commonly occur in written texts, particularly, the secondary senses of pronouns and kinship terms when their meanings are determined on the basis of the use in the receptor language and not on the basis of the form in the source language. Proper names in Indonesian which are mostly culture-based bear ambiguities the translating substitute devices that refer to those particular proper names in a text. Accordingly, some ways on how to deal with the differences are recommended in each topic discussed.